Cold orbital forging of gear rack. (October 2016) - Han, Xinghui; Hu, Yaxiong; Hua, Lin
Abstract: At present, gear rack is manufactured mainly by cutting method while its precision plastic forming method has not been reported. This paper proposes an innovative cold orbital forging method for manufacturing gear rack, in which the complicated teeth of gear rack are forged by the highly dynamic rocking tool under straight line path. Firstly, a universal method for designing the rocking tool under straight line path is proposed according to the forming mode and contacting mode between the rocking tool and component, i.e., one side of the component is ultimately overall formed by the overall contact (it is achieved by the incremental deformation) between the corresponding side of the rocking tool and component. Based on this universal method, the rocking tool in cold orbital forging of gear rack is accurately designed. Secondly, the mathematical model and method for interference examinations between the rocking tool and gear rack are developed and the interference amount and interference zone are calculated. Thirdly, to eliminate the interference between the rocking tool and gear rack so as to guarantee the forming accuracy of gear rack, a dynamic envelope forming principle is proposed and an innovative forming mode of gear rack is correspondingly developed, i.e., all the time-varying interference zones in the rocking tool are cut one by one and the ultimate tooth surface (planar) of gear rack is incrementally formed by the local contact between a series of modified surfaces (nonplanar) of the rocking tool and tooth surface of gear rack. Based on this proposed dynamic envelope forming principle, the mathematical model and method for modifying the rocking tool are developed and the dynamic envelope forming of gear rack is achieved successfully. The FE simulations and experiments of cold orbital forging of gear rack are conducted. The results demonstrate that the proposed cold orbital forging method for manufacturing gear rack in this paper is effective and cold orbital forging shows great potential in manufacturing gear rack. Highlights: Innovative cold orbital forging method for manufacturing gear rack is proposed. Universal method for designing rocking tool under straight line path is proposed. Interference examination model between rocking tool and gear rack is developed. Dynamic envelope forming principle and innovative forming mode are developed. Mathematical model and method for modifying rocking tool are developed.